2018
DOI: 10.1021/acs.jpcc.8b02685
|View full text |Cite
|
Sign up to set email alerts
|

Electrooxidation of Glycerol on Gold in Acidic Medium: A Combined Experimental and DFT Study

Abstract: Glycerol is a byproduct of biodiesel production and an abundant feedstock for the synthesis of high-value chemicals. A promising approach for valorization of glycerol is electrooxidation on gold. In this work, we investigate electrooxidation of glycerol on gold in acidic media using cyclic voltammetry and density functional theory calculations. Experimentally, we observe activity for electrooxidation above a potential of 0.5 V versus the reversible hydrogen electrode (RHE). A Pourbaix diagram is calculated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(86 citation statements)
references
References 47 publications
13
73
0
Order By: Relevance
“…It has been considered for a long time that platinum was unavoidable in such media to activate the dissociative adsorption of alcohols at its surface (Hogarth and Ralph, 2002; Venancio et al, 2002; Léger et al, 2005), leading to adsorbed species which could be further oxidized and desorbed at relatively high rates. However, it has been proposed recently that gold could also present some activity toward glycerol electrooxidation in acidic medium (Valter et al, 2018). This result was very surprising as previous works established that gold wasn't an active material in acidic media for alcohol oxidation (Beden et al, 1987; Kwon et al, 2011a).…”
Section: Electro-oxidation Of Glycerol In Acidic Mediamentioning
confidence: 99%
“…It has been considered for a long time that platinum was unavoidable in such media to activate the dissociative adsorption of alcohols at its surface (Hogarth and Ralph, 2002; Venancio et al, 2002; Léger et al, 2005), leading to adsorbed species which could be further oxidized and desorbed at relatively high rates. However, it has been proposed recently that gold could also present some activity toward glycerol electrooxidation in acidic medium (Valter et al, 2018). This result was very surprising as previous works established that gold wasn't an active material in acidic media for alcohol oxidation (Beden et al, 1987; Kwon et al, 2011a).…”
Section: Electro-oxidation Of Glycerol In Acidic Mediamentioning
confidence: 99%
“…Considering the recent advances in the theoretical description of glycerol adsorption, the studies have shown the complexity of the molecular interaction of glycerol with different sites symmetries, and consequently a complex GEOR mechanism. [36,37] Therefore, due to the molecular structure, it is expected that glycerol molecule decomposition on platinum surface involves several reaction intermediates including products resulting from CÀ C bond cleavage even at low potentials. This cleavage has been already observed for two-carbon alcohols (ethanol, ethylene glycol) at low potentials.…”
Section: General Analysis Of Voltammetric Features Of the Glycerol Oxmentioning
confidence: 99%
“…Computationally, it was observed the partial dehydro genation started in the potential range below 1.0 V vs. RHE. The formation of dihydroxyacetone, 2,3 dihydroxy 2 propenal and glyceraldehyde was observed and proposed at 0.39, 0.39, and 0.60 V vs. RHE, respectively, whereas the complete dehydrogena tion to carbon monoxide (CO) happened at 0.50 V vs. RHE (Valter et al, 2018). The presence of this CO specified that the C C bond was broken which means low selectivity in C 3 species in the pro cess.…”
Section: Ph Of Electrolytementioning
confidence: 99%
“…The glycerol electro oxidation rate occurred twice as much in alkaline medium on both Au and Au PVC elec trodes compared to an acidic medium in which oxidation only hap pened once on Au electrode (Othman and Ahmad, 2015). However, more recently, Valter et al (2018) proposed that Au electrodes also exhibited catalytic activity in acidic medium. Instead of using 0.5 M H 2 SO 4 (Beden et al, 1987; Kwon et al, 2011a), they used 0.1 M HClO 4 as supporting electrolyte.…”
Section: Ph Of Electrolytementioning
confidence: 99%